Desenvolvimento da cultura do milho sob níveis de densidade e tensões de água em latossolo vermelho de cerrado - Nunes, João Angelo Silva (2014)
Inadequate management of soil and water can cause changes in the physical characteristics of the soil, resulting in losses in agricultural production. The objective was evaluate the effect of soil bulk density levels and water tensions in growth and yield characteristics of maize (Zea mays L.) under controlled conditions. The experiment was conducted in a greenhouse at the Federal University of Mato Grosso, Campus Rondonopolis, in experimental design with randomized blocks, in 5² factorial arrangement and is composed of combinations of bulk densities of soil (1.0, 1.2, 1.4, 1.6 and 1.8 Mg m-3) and water tensions in the soil (10, 20, 30, 40 and 50 kPa) resulting in 13 treatments with four replications. Was utilized an Oxisol collected from 0 to 0.2 m deep. The intermediate layer was of soil compacted with the aid of a hydraulic press and the rings of the bottom and upper part were filled with soil in the density of 1.0 Mg m-3. The tensiometers were installed at a depth of 15 cm, remaining in the central region of the compacted layer. Evaluations were carried out at 30, 45, 67 and 104 days after sowing. In the initial development of the maize crop was isolated effect for soil bulk density levels. In the four reviews of stem diameter was performed isolated effective for soil bulk density. For the number of leaves, was isolated influence in the two first evaluations carried out, and from 67 days after sowing there was no significant difference in the levels of bulk density and water tension in the soil. For height and chlorophyll index it was observed that at the end the crop cycle there was isolated effect of water tensions in the soil. The dry mass production the aerial part and roots in maize was limited by increased water tension in the soil, and for the soil bulk density the critical limit observed was 1.30 Mg m-3. The increased soil bulk density was more harmful in initial development of corn plants, while at the end the cultivation cycle was obtained higher effect of water tensions applied to the soil in relation to the vegetative characteristics of corn.